Urban Modernity: Cultural Innovation in the Second Industrial Revolution - Levin, Miriam R. (The MIT Press, 2012)
How Paris, London, Chicago, Berlin, and Tokyo created modernity through science and technology by means of urban planning, international expositions, and museums.